Breastmilk influences development and composition of the oral microbiome. Issue 1 (31st December 2022) - Butler, Catherine A.; Adams, Geoffrey G.; Blum, Jordan; Byrne, Samantha J.; Carpenter, Lauren; Gussy, Mark G.; Calache, Hanny; Catmull, Deanne V.; Reynolds, Eric C.; Dashper, Stuart G.
ABSTRACT: Background: Human microbiomes assemble in an ordered, reproducible manner yet there is limited information about early colonisation and development of bacterial communities that constitute the oral microbiome. Aim: The aim of this study was to determine the effect of exposure to breastmilk on assembly of the infant oral microbiome during the first 20 months of life. Methods: The oral microbiomes of 39 infants, 13 who were never breastfed and 26 who were breastfed for more than 10 months, from the longitudinal VicGeneration birth cohort study, were determined at four ages. In total, 519 bacterial taxa were identified and quantified in saliva by sequencing the V4 region of the bacterial 16S rRNA genes. Results: There were significant differences in the development of the oral microbiomes of never breastfed and breastfed infants. Bacterial diversity was significantly higher in never breastfed infants at 2 months, due largely to an increased abundance of Veillonella and species from the Bacteroidetes phylum compared with breastfed infants. Conclusion: These differences likely reflect breastmilk playing a prebiotic role in selection of early-colonising, health-associated oral bacteria, such as the Streptococcus mitis group. The microbiomes of both groups became more heterogenous following the introduction of solid foods.